The grammatical intensification signals in adjectives and adverbs in English and Waray a contrastive analysis - Homeres, Andres Factoranan 1936- (1969)
This study described and contrasted the grammatical intensification signals in adjectives and adverbs in English and Waray according to form, meaning and distribution. Similarities and differences in varying degrees were revealed in the parallel inventory of the grammatical intensification signals in English and Waray. The findings in the concluding part were drawn from the results of the linguistic analysis systematically treated. Particular learning problems were defined to make the teacher aware of the predicted difficulties for both teacher and language learner so that teaching these particular grammatical structures will be better.